Symmetry and exact solution of heat-mass transfer equations in thermonuclear plasma - Cherniga, R.M.; Wilhetmsson, H. (Український математичний журнал, 1996)
For the nonlinear system of partial differential equations, which describes the evolution of temperature and density in TOKAMAK plasmas, multiparameter families of exact solutions are constructed. The solutions are constructed by the Lie-method reduction of initial systems of equations to a system of ordinary differential equations. Examples of non-Lie ansätze and exact solutions are also presented.